Pemanfaatan Biji Nangka dan Biji Kedelai sebagai Bahan Baku Pembuatan Tepung - Nila Tanyela Berghuis; Ujang Ahmad Soleh; Zulfikar Fauzan Ali; Tuti Purnama Elia; Yeni Novita Sari; Meidiana Budiawati; Rika Febriyanti Hermana; Miftah Khoirunnisa; Syifa Fadlillah (Stannum : Jurnal Sains dan Terapan Kimia, 2022)
The accumulation of plastic waste and excessive use of plastic is a common environmental issue in Indonesia. Plastics are synthetic polymers that are stable, water-resistant, light, flexible, and strong, but are very difficult to be broken down by microorganisms. Decomposition of plastic waste by burning can cause other environmental issues and during the combustion process can produce dioxin compounds that are harmful to health. An available and affordable alternative to reduce the use of plastic is by using bioplastics. Bioplastics are plastics made from natural materials that can be broken down by microorganisms, so they are more environmentally friendly than commercial plastics. Generally, the main ingredients of making bioplastics are starch or chitosan. The source of starch used in this project comes from cassava peel waste. In this project, researchers also utilize waste from chicken egg-shells. The function of adding eggshell waste is to give biodegradable plastic hard characteristics. The ratio between cassava peel and egg shell used was 1:0, 1:1, 1:3, and 1:5. With a 1:1 ratio is the most optimal. the addition of egg shells with the right ratio (1:1) made the ability of biodegradation of bioplastics to increase. The results of the Tensile Strength Test of Bioplastic Samples with a ratio of 1:0, 1:1, 1:3 and 1:5 are 9.2 x10-3 kgf/cm2, 4.4 x10-3 kgf/cm2, 2 x10-3 kgf/cm2 and 2 x10 -3 kgf/cm2.